Assessment of portable biogas plants for their energy production and emission reduction potential - Iwin K Augastian (Academy of Climate Change Education and Research, 2016)
Climate change is one of the serious issues faced currently by humanity. The uncontrolled emission of Green House Gases play a major role in global warming, which eventually leads to climate change. The unscientific methods of waste disposal has serious environmental impacts by continuous emission of GHGs leading to global warming. Households constitute the basic unit in urban energy consumption and waste generation. Anaerobic digestion of the organic fraction of household wastes in a decentralised manner using biogas plants offers great scope in waste management and generation of cheap renewable energy for domestic cooking. The investigations revealed that average amount of organic waste generated per household was 5.28 kg (5 member family) and that of a hostel mess was 24.9 kg (40 inmates). Kitchen wastes in Kerala had a major fraction as liquids and per capita food waste generation in households and hostel mess were 42 g and 153 g, respectively. Average TS of kitchen waste was found as 82 gL-1 and the average pH was found as 3.86. Average C: N ratio of the kitchen waste was found as 53.88:1. The minimum ratio of kitchen waste and inoculum required for a successful start-up of anaerobic system was 1:5. Biogas productivity of kitchen waste was found as 57.57 LL-1and the average specific biogas production from kitchen waste was estimated as 989.05 L kgTS -1. 80-90 % of the potential of kitchen waste to generate biogas can be utilized if the HRT was in range of 40-50 days. Thus it is preferable to have a HRT in the range of 40-50 days for domestic biogas plants working on kitchen wastes. Average methane content in biogas produced from kitchen waste was enumerated as 62.18%. The preliminary biomethanation studies revealed the high potential of kitchen waste to generate biogas. Portable biogas plants are easily shifted and installed, require less space and can be placed conveniently in urban conditions. The four types of portable biogas models used in the study were floating gas holder type (PBP1), floating gas holder type with water seal (PBP2), fixed gas holder type (PBP3) and KAU portable split biogas plant (PBP4). The four portable biogas plants (PBPs) were evaluated by operating them at 50 and 40 day HRT. An increase in mean volumetric biogas production was observed in 40-day HRT compared to 50 day HRT in all PBPs. The maximum increase in biogas production was in PBP4 (34.4